A comparative electrochemical study of non-enzymatic glucose, ascorbic acid, and albumin detection by using a ternary mesoporous metal oxide (ZrO2, SiO2 and In2O3) modified graphene composite based biosensor. Issue 7 (22nd January 2021) - Fatema, Kamrun Nahar; Oh, Won-Chun
Abstract : In this study, we present an electrochemical investigation of a ternary mesoporous metal oxide (ZrO2, SiO2 and In2 O3 ) modified graphene composite for non-enzymatic glucose, ascorbic acid, and albumin detection in urine at physiological pH. Abstract : In this study, we present an electrochemical investigation of a ternary mesoporous metal oxide (ZrO2, SiO2 and In2 O3 ) modified graphene composite for non-enzymatic glucose, ascorbic acid, and albumin detection in urine at physiological pH. Synergetic property of ZrO2 –Ag–G–SiO2 and In2 O3 –G–SiO2 were investigated via cyclic voltammetry (CV) using FTO glass and copper-foil electrodes with no prerequisite of solid antacid expansion. The mesoporous ZrO2 –Ag–G–SiO2 and In2 O3 –G–SiO2 composites were synthesized and characterized using XRD, SEM, TEM, Raman spectroscopy, XPS, DRS, BET, and photocurrent measurements. Upon increasing the glucose concentration from 0 to 3 mM, CV results indicated two anodic peaks at +0.18 V and +0.42 V versus Ag/AgCl, corresponding to Zr 3+ and Zr 4+, respectively, considering the presence of glucose in urine. Moreover, the effects of high surface area In2 O3 –G–SiO2 were observed upon the examination of ZrO2 –Ag–G–SiO2 . In2 O3 –G–SiO2 demonstrated a decent electrochemical pattern in glucose, ascorbic acid, and albumin sensing. Nevertheless, insignificant synergistic effects were observed in In2 O3 -G, ZrO2 -G, and ZrO2 –G–SiO2 . In2 O3 –G–SiO2 performed well under a wide range of electrolytes and urine, and showed no activity toward uric acid, suggesting potential for biodetection in urine.